Implications of the search for optical counterparts during the first six months of the Advanced LIGO's and Advanced Virgo's third observing run: possible limits on the ejecta mass and binary properties. Issue 1 (10th December 2019) - Coughlin, Michael W; Dietrich, Tim; Antier, Sarah; Bulla, Mattia; Foucart, Francois; Hotokezaka, Kenta; Raaijmakers, Geert; Hinderer, Tanja; Nissanke, Samaya
ABSTRACT: GW170817 showed that neutron star mergers not only emit gravitational waves but also can release electromagnetic signatures in multiple wavelengths. Within the first half of the third observing run of the Advanced LIGO and Virgo detectors, there have been a number of gravitational wave candidates of compact binary systems for which at least one component is potentially a neutron star. In this article, we look at the candidates S190425z, S190426c, S190510g, S190901ap, and S190910h, predicted to have potentially a non-zero remnant mass, in more detail. All these triggers have been followed up with extensive campaigns by the astronomical community doing electromagnetic searches for their optical counterparts; however, according to the released classification, there is a high probability that some of these events might not be of extraterrestrial origin. Assuming that the triggers are caused by a compact binary coalescence and that the individual source locations have been covered during the EM follow-up campaigns, we employ three different kilonova models and apply them to derive possible constraints on the matter ejection consistent with the publicly available gravitational-wave trigger information and the lack of a kilonova detection. These upper bounds on the ejecta mass can be related to limits on the maximum mass of the binary neutron star candidate S190425z and to constraints on the mass-ratio, spin, and NS compactness for the potential black hole–neutron star candidate S190426c. Our results show that deeper electromagnetic observations for future gravitational wave events near the horizon limit of the advanced detectors are essential.